2005
DOI: 10.1155/s1110662x05000267
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ferrous ions on the efficiency of aqueous photocatalytic oxidation of 2‐ethoxy ethanol

Abstract: Abstract. The complex influence of ferrous ions on the efficiency of aqueous photocatalytic oxidation (PCO) of 2-ethoxyethanol (2-EE) was examined. A drastic efficiency increase at lower concentrations of ferrous ions was observed to change to a sharp decrease at higher concentrations. An explanation was proposed for the observed phenomena based on the low sensitivity of the pollutant towards radical-oxidation reactions and the competitive adsorption of metallic ions and 2-EE on the TiO 2 surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Several previous studies have reported higher PCO rates following the addition of small amounts of ferrous [16,17,19] and some other multivalent cations [20,21]. Our previous studies showed the positive role of ferrous ions, abundantly present in waters under anoxic reductive conditions, such as groundwater or landfill leachate, at low concentrations in the efficiency of PCO of methyl tert-butyl ether and 2-ethoxyethanol [22]. The results of the more detailed investigation, given here, extend knowledge of the influence of iron ions on pollutants of various types and show the complex character of the dependence of the PCO efficiency on the concentration of iron ions.…”
Section: Introductionmentioning
confidence: 75%
“…Several previous studies have reported higher PCO rates following the addition of small amounts of ferrous [16,17,19] and some other multivalent cations [20,21]. Our previous studies showed the positive role of ferrous ions, abundantly present in waters under anoxic reductive conditions, such as groundwater or landfill leachate, at low concentrations in the efficiency of PCO of methyl tert-butyl ether and 2-ethoxyethanol [22]. The results of the more detailed investigation, given here, extend knowledge of the influence of iron ions on pollutants of various types and show the complex character of the dependence of the PCO efficiency on the concentration of iron ions.…”
Section: Introductionmentioning
confidence: 75%
“…The data available from published sources showed the reduction of decomposition rate with the increase of multivalent metallic ions concentration. However Klauson and Preis [19] observed an increased efficiency of PCO of methyl tert-butyl ether and 2ethoxyethanol at low concentrations of ferrous ions. The role of ferrous ions in the PCO efficiency was studied here.…”
Section: Introductionmentioning
confidence: 94%
“…Aqueous photocatalytic oxidation experiments were carried out using the experimental setup described in the authors' previously reported works . Titanium dioxide (P25 Evonik) was fixed to a glass plate by spraying a suspension and drying.…”
Section: Methodsmentioning
confidence: 99%
“…Aqueous photocatalytic oxidation experiments were carried out using the experimental setup described in the authors' previously reported works. 51 Titanium dioxide (P25 Evonik) was fixed to a glass plate by spraying a suspension and drying. A Philips Actinic 365-nm low-pressure mercury lamp was used as the light source; its irradiance was measured to be around 1 mW cm −2 using an Ocean Optics USB 2000+ radiometer.…”
Section: Physico-chemical Treatment Methodsmentioning
confidence: 99%